Composition and functioning of the soil microbiome in the highest altitudes of the Italian Alps and potential effects of climate change. Issue 3 (3rd March 2022) - D'Alò, Federica; Baldrian, Petr; Odriozola, Iñaki; Morais, Daniel; Větrovský, Tomáš; Zucconi, Laura; Ripa, Caterina; Cannone, Nicoletta; Malfasi, Francesco; Onofri, Silvano
Abstract: As the European Alps are experiencing a strong climate warming, this study analyzed the soil microbiome at different altitudes and among different vegetation types at the Stelvio Pass (Italian Alps), aiming to (i) characterize the composition and functional potential of the microbiome of soils and their gene expression during the peak vegetative stage; (ii) explore the potential short-term (using open-top chambers) and long-term (space-for-time substitutions) effects of increasing temperature on the alpine soil microbiome. We found that the functional potential of the soil microbiome and its expression differed among vegetation types. Microbial α-diversity increased along the altitudinal gradient. At lower altitude, shrubland had the highest proportion of fungi, which was correlated with higher amounts of CAZymes, specific for degrading fungal biomass and recalcitrant plant biopolymers. Subalpine upward vegetation shift could lead a possible loss of species of alpine soils. Shrub encroachment may accelerate higher recalcitrant C decomposition and reduce total ecosystem C storage, increasing the efflux of CO2 to the atmosphere with a positive feedback to warming. A total of 5 years of warming had no effect on the composition and functioning of microbial communities, indicating that longer-term warming experiments are needed to investigate the effects of temperature increases on the soil microbiome. Abstract : Alpine shrub encroachment may result in the loss of soil microbial species and more recalcitrant C decomposition, which may have a positive feedback to warming.